Cinema 4D S22 Essential Training: Motion Graphics. - Needham, Andy (linkedin.com, 2020)
Design compelling motion graphics using the MoGraph toolset in Cinema 4D. Learn how to use both essential features and new features available in Subscription Release 22 (S22).